Anmeldelser - Ramsten, Märta (Danish Yearbook of Musicology, 1998)
Review of: Doris Stockmann & Jens Henrik Koudal (eds.): Historical Studies on Folk and Traditional Music (Acta Etnomusicologica Danica, vol. 8). Danish Folklore Archives & Museum Tusculanum Press, København 1997.